Editorial introduction IST'2009 - Kalogirou, Soteris A. (My University, 2010)
This special issue of Renewable Energy compiled a selection of papers presented at the 9th Institute of Solar Technology (IST) National Conference on Renewable Energy Sources held in Geroskipou, Cyprus, 26–28 March 2009. This conference was jointly organized by the Department of Mechanical Engineering and Materials Sciences and Engineering of the Cyprus University of Technology, the scientific Technical Chamber of Engineers, Geroskipou Municipality and the Institute of Solar Technology, Greece. The IST’09 conference held in Geroskipou addressed a wide range of topics related to renewable energy sources ranging from energy in buildings, solar thermal applications, photovoltaics, geothermal systems, fuel cells and hydrogen, policy and desalination. This special issue presents papers dealing with the most current renewable energy systems. As the conference is National, all papers were delivered in Greek. Authors willing to have their papers considered for publication in this special issue have translated their work in English and submitted it to the Guest Editor. All papers were then blind reviewed from independent reviewers. The papers presented in this special issue are a selection of the best papers from the ones submitted. Special thanks are extended to the authors for their valuable contributions and to the reviewers for their useful feedback provided through the process.
Keywords: Renewable energy systems; Conference